PENYAJIAN PROGRAM SIARAN BERMUATAN KEKERASAN PADA PROGRAM BERITA “KABAR SIANG” TV ONE DAN “METRO SIANG” METRO TV BULAN MARET 2014 - Kristiyawanto . (Saraswati)
The purposes of the research about “Penyajian Program SiaranBermuatan Kekerasan pada Program Berita „Kabar Siang‟ TV ONE dan „Metro Siang‟ METRO TV Bulan Maret 2014” are a) to know the type, kind and prosentase of the presentation in the news program “Kabar Siang” and “Metro Siang” on March 2014; b) to know the presentation and violence content prosentase in the news “Kabar Siang” and “Metro Siang” on March 2014; c) to know the reason why violence content is still showed. This research uses quantitative and qualitative method by using descriptive content analysis. Based on the result of study, the writer can get conclusion that in March 2014 in the news “Kabar Siang” and “Metro Siang” present violence contents about 6% from 1254 news titles. Kind of non physical content about 70 % present with the news presentation format package. The dominant audio element in the news presentation that contain violence is narration and its visual element long shot, medium shot, straight angle and high angle.Keywords : news, violence, presentation, audiovisual